A phase II trial of azacitidine with ipilimumab, nivolumab, or ipilimumab and nivolumab in previously untreated myelodysplastic syndrome - Ian M. Bouligny; Guillermo Montalban-Bravo; Koji Sasaki; Naval Daver; Elias Jabbour; Yesid Alvarado; Courtney D. DiNardo; Farhad Ravandi; Gautam Borthakur; Prithviraj Bose; Naveen Pemmaraju; Steven Kornblau; et al. (Haematologica, 2025)
Not available.